Pengaruh Fasilitas Pembayaran Non-Tunai di Kawasan Kuliner Dipati Ukur Kota Bandung terhadap Kepuasan Konsumen - Selvia, Nanda (International Journal Administration, Business & Organization, 2022)
The growth of Small and Medium Enterprise (SME) in Indonesia is increasing day by day, this has resulted in SME’s owners having to give their best in order to satisfy consumers and increase their business potential. There are several things that can support the fulfillment of customer satisfaction, one of which is providing the facilities needed by consumers. Considering the development of an all-digital era, many people are now switching to using cashless transaction facilities to speed up the transaction process. Thus, the research was conducted to find out how the implementation of cashless payment facilities and its effect on consumer satisfaction. Researchers used a descriptive method with a quantitative approach through data, which was obtained from filling out questionnaires by consumers in the Dipati Ukur culinary area of ​​Bandung City as many as 106 respondents. The analysis technique used is descriptive analysis test, normality test, linearity test, heteroscedasticity test, simple linear regression test, coefficient of determination test, and hypothesis testing using IBM SPSS 23 software. Based on the results of data analysis, it can be concluded that there is a positive influence between cashless payment facilities to customer satisfaction. This means that if the application of cashless payment facilities is optimized, then customer satisfaction will also increase.